ALLERGIC MANIFESTATION IN OUTPATIENT ORAL SURGERY - IMPLICATIONS OF LOCAL ANESTHETICS - Oana Elena Ciurcanu; Doriana Agop-Forna; Octav Mihai Boaru; Topoliceanu Claudiu; Monica Mihaela Scutariu (Romanian Dental Association for Education, 2019)
Nowadays the allergic accidents to the local anesthetics are exceptional and rare. The additional agents can be a source of allergy. Also the individual factors can favourise the onset of the allergic reactions. The quest of a patient with history of allergic reactions will be included in the medical record. The diagnostic of allergy must be confirmed by using allergy tests, by the selection of a proper and non-allergenic anesthetic, and by ensuring the optimal operatory comfort both for the patient and the dental practitioner. Despite the low frequency of the allergic accidents in the oral surgery (0, 96 % minor allergic reactions, 0,032 % severe allergic reactions), they must be considered due to the potential risk for the patient' vital prognostic. The allergy tests (Prick test, IDR, provoking tests) are requested to remove the contraindicated materials with high risk for the initiation of the allergic reactions.